Altitudinal divergence in maternal thermoregulatory behaviour may be driven by differences in selection on offspring survival in a viviparous lizard - Uller, T; While, G; Cadby, C; Harts, A; O'Connor, K; Pen, I; Wapstra, E (2011)
Plastic responses to temperature during embryonic development are common in ectotherms, but their evolutionary relevance is poorly understood. Using a combination of field and laboratory approaches, we demonstrate altitudinal divergence in the strength of effects of maternal thermal opportunity on offspring birth date and body mass in a live-bearing lizard (Niveoscincus ocellatus). Poor thermal opportunity decreased birth weight at low altitudes where selection on body mass was negligible. In contrast, there was no effect of maternal thermal opportunity on body mass at high altitudes where natural selection favored heavy offspring. The weaker effect of poor maternal thermal opportunity on offspring development at high altitude was accompanied by a more active thermoregulation and higher body temperature in highland females. This may suggest that passive effects of temperature on embryonic development have resulted in evolution of adaptive behavioral compensation for poor thermal opportunity at high altitudes, but that direct effects of maternal thermal environment are maintained at low altitudes because they are not selected against. More generally, we suggest that phenotypic effects of maternal thermal opportunity or incubation temperature in reptiles will most commonly reflect weak selection for canalization or selection on maternal strategies rather than adaptive plasticity to match postnatal environments. © 2011 The Author(s). Evolution © 2011 The Society for the Study of Evolution.